Pandangan Gereja Katolik Tentang Operasi Plastik dan “Implementasi Moralitas Manusia Sebagai Citra Allah” - Megawati Naibaho; Kristiana Mendröfa; Laurensia Muliati Lase (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2025)
Human being was created by God in His image and endowed with noble dignity. God requests human being to care and respect their body as God's temple. One challenge human dignity to preserve the dignity was plastic surgery, especially in order to change the gender. The method used in this research is the literature review. The authors gather information about plastic surgery through books, articles or journals, the internet, and the Church Documents. The researchers found that the Catholic Church supports the plastic surgery with the aim of repairing defective body organs to support optimizing function. Thus, this research purposes to promote moral value so that the people are able to choose the right goals for plastic surgery. The Catholic Church endorses plastic surgery which is useful to preserve human dignity as the image of God. The researchers hope that this study will be valuable in providing knowledge about plastic surgery, such as reconstructive surgery and aesthetic surgery. Hence, the plastic surgery requires being prepared wisely, both from medical personnel who will perform the plastic surgery and the patients who will undergo plastic surgery. This research affords moral guidance in plastic surgery.